Observing the signatures of AGB s-process nucleosynthesis in planetary nebulae: An origins story - Dinerstein, Harriet L. (Frontiers in Astronomy and Space Sciences, 2022)
I relate an anecdotal history of the beginnings of a new initiative in studies of the chemical composition of planetary nebulae: namely, investigating abundances of elements beyond the iron-peak through infrared spectroscopy. In some planetary nebulae many of these elements display enrichments due to neutron capture reactions within the progenitor stars. This snippet of history provides an example of how science advances from the convergence of improvements in instrumentation, cross-over between fields, and constructive interaction between theory and observation. It also highlights the fact that terra incognita and discovery space remains even in seemingly well-established fields of science.